Evaluation of Public Sector Policy: A Case Study on the Dissolution of Villages in Areas Affected by the Mudflow Disaster in Sidoarjo, Indonesia - Andjar Surjadianto; Nuri Herachwati; Fiona Niska Dinda Nadia (Dinasti International Journal of Education Management And Social Science, 2025)
The 2006 hot mudflow disaster in Sidoarjo, Indonesia, triggered significant social, political, economic, and administrative challenges for both the local government and the affected communities. Among the impacts, several villages and hamlets no longer met the criteria for territorial and population standards, necessitating an urgent resolution to prevent further socio-economic complications and ensure the optimization of government services. This situation has implications for both local governance and population administration. This research adopts a qualitative approach, utilizing secondary data analysis to evaluate the policy response to the villages and hamlets impacted by the mud disaster in Sidoarjo Regency. The findings reveal that the local government has implemented mitigation processes for the affected areas in alignment with the prevailing regulations. However, various policy outcomes were identified, including administrative, governmental, economic, social, cultural, and environmental impacts. Notably, the top-down approach to village and district amalgamation presents anomalies that should prompt the Central Government to reassess its policy-making processes, ensuring that future decisions are more inclusive of community involvement. Additionally, the Sidoarjo Regency Government is urged to monitor and facilitate the long-term sustainability of the policy’s effects, ensuring that administrative and social cohesion is achieved in the merged areas. This research contributes to Sustainable Development Goal (SDG) #11, which seeks to foster inclusive, safe, resilient, and sustainable cities and communities.